Reinterpretasi Keluaran 28 Tentang Etika Berpakaian Hamba Tuhan di Mimbar Menghadapi Era Disrupsi - Lucky Yohanes Siswandi; Yuli Wahyu Setyowati; Ragil Kristiawan (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This study reformulates a reinterpretation of Exodus 28 as the foundation for the pulpit dressing ethics of ministers facing the era of disruption. Previous research leaves a significant gap, focusing primarily on spiritual leadership or general textual reception without providing a practical framework for contemporary ministerial attire. Employing a qualitative library research method, this study integrates a Hebrew exegetical analysis of Exodus 28, a literature review on disruption-era dressing phenomena, and a hermeneutical reinterpretation distinguishing between form and theological function. The findings reveal three universal theological principles within Exodus 28: holiness as separation from the profane, representation in bearing the people, and covering nakedness as respect for the ministry calling. Ultimately, this study contributes to practical theology and biblical studies by establishing an ethical framework that balances personal freedom of expression with theological responsibility. It serves as a concrete guide for training prospective ministers, fostering critical-theological awareness in choosing ministry attire amid modern challenges.